Elucidating cytotoxic effects of quercus infectoria gall extract on temozolomide-resistant glioma cells - Muhamad, Norhazilah (2023)
Glioblastoma (GB) is a highly aggressive primary brain tumour characterized by a high mortality rates and poor prognosis. The first-line chemotherapy for GB is temozolomide (TMZ). However, drug resistance, unwanted side effects and GB recurrence become the major drawbacks of chemotherapy. Hence, medicinal plants are used as alternative treatments which offer wide accessibility and lesser side effects. From a previous study, Quercus infectoria gall methanol extract (QIM) has demonstrated its potent in vitro antiproliferative activity against human glioma cells. Thus, this study aims to elucidate the anticancer compounds within QIM and explore the underlying anticancer mechanisms. Additionally, QIM's potential to enhance the therapeutic effects of TMZ in combination treatments, particularly against TMZresistant (DBTRG-05MG) and TMZ-sensitive (U-87MG) glioma cell lines was conducted. Phytochemicals screening, phytoconstituents characterization by FT-IR and LC-MS and DPPH assay were done to evaluate the bioactivity of QIM. Antiproliferative activity of QIM and TMZ treatment against glioma and glial (SVG p12) cells were determined using MTT assay. IC50 values were then determined from a dose-response curve and employed for combination treatment. The combined effect of the treatment was determined based on their combination index (CI) using CompuSyn software. Anticancer mechanisms of single and combined treatment were evaluated by AO/PI staining for determination of the mode of cell death, clonogenic assay for reproductive ability, wound scratch assay for anti-invasion and RT-qPCR to evaluate the gene expression profiles associated with apoptosis, autophagy, antiinvasion, angiogenesis, antioxidant responses and drug resistance mechanisms. The findings suggested that the major phytoconstituent in QIM was gallotannin with a functional group, named phenols. QIM showed robust DPPH radical scavenging activity (EC50 = 16.90 μg/mL) comparable to gallic acid (EC50 = 17.33 μg/mL). QIM exhibited better cytotoxicity against U-87MG (IC50 = 20.5 μg/mL) compared to DBTRG-05MG (IC50 = 21.4 μg/mL) and cytoselective against SVG p12 cells (no IC50 detected). Notably, TMZ-resistant was shown by DBTRG-05MG (IC50 = 480.30 μg/mL) which require higher concentration compared to U-87MG (IC50 = 56.14 μg/mL). Remarkably, combination treatment significantly reduced the proliferation of both glioma cell lines when compared to TMZ alone and it demonstrated a synergistic effect (CI<1). Moreover, both single and combined treatments induced apoptosis in glioma cells, characterized by apoptotic morphological changes and upregulation of apoptosis-related genes (BAX and CASP3). QIM also inhibited autophagy by downregulating the LC3B gene. Additionally, the suppression of wound healing and the downregulation of the invasion gene (ADAM17) indicated that the combined treatment inhibited cell migration and metastasis. The significant downregulation of angiogenesis-related genes (VEGFA and ANGPT1), which restricted the availability of nutrients and oxygen to cancer cells, further supported these effects. Combination treatment also significantly increased TMZ's therapeutic efficacy by downregulating drug-resistant genes (MGMT, MRP and PI3KA), resulting in greater cell proliferation inhibition. In conclusion, QIM exhibits selective anticancer activity through apoptosis and autophagy pathways, and the combination treatment of QIM and TMZ exerted a synergistic effect in glioma cells.